Novel HIT antibody detection method using Sonoclot® coagulation analyzer. Issue 1 (January 2015) - Wanaka, Keiko; Asada, Reiko; Miyashita, Kumiko; Kaneko, Makoto; Endo, Hirokazu; Yatomi, Yutaka
Abstract Introduction Since heparin-induced thrombocytopenia (HIT), caused by the generation of antibodies against platelet factor 4 (PF4)/heparin complexes (HIT antibodies), may induce serious complications due to thrombosis, a prompt diagnosis is desirable. Functional tests with platelet activation to detect HIT antibodies are useful for diagnosis of HIT, in particular 14C-selotonin release assay (SRA). However, they are complicated and so can be performed only in limited laboratories. We tested if a blood coagulation test using Sonoclot® analyzer can serve for the detection of HIT antibodies. Materials and Methods A murine monoclonal antibody (HIT-MoAb) against PF4/heparin complexes was used as an alternative to human HIT antibodies. To the mixture of HIT-MoAb and heparin (0.5 U/mL, final), whole blood obtained from a healthy volunteer was added, and then the activated clotting time (ACT), clot rate (CR), and area under the curve (AUC) were measured with Sonoclot® analyzer for 30 minutes. Results The HIT-MoAb (30 to 100 μg/mL, final) concentration dependently suppressed the anticoagulation activity (prolongation of ACT and decrease of CR and AUC) of heparin. Conclusions The suppression of anticoagulation effect of heparin by HIT-MoAb was demonstrated by measurements using Sonoclot® analyzer. This method may provide a new tool for screening of HIT antibodies.